2014
DOI: 10.1039/c4dt01407c
|View full text |Cite
|
Sign up to set email alerts
|

Femtosecond spectroscopy of the dithiolate Cu(ii) and Ni(ii) complexes

Abstract: Femtosecond spectroscopy was applied to study the ultrafast dynamics for the excited states of dithiolate Cu(ii) and Ni(ii) complexes. The detailed information on the initial steps after the absorption of a photon by the metal complexes is of fundamental importance to understand the mechanism of photochemical reactions. The fast processes for the dithiolate complexes have hardly been studied. In this review the spectra of transients and their lifetimes will be presented. For example, the xanthogenate Ni(S2COEt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 74 publications
1
6
0
Order By: Relevance
“…A very recent study reported ligand-based fluorescence from a Ni II complex in solution without direct metal contribution . Weakly luminescent Ni II compounds emitting from triplet states were found in two other recent works, albeit only in the solid state, in which the processes illustrated in Figure a/b are largely suppressed. , Studies in fluid solution at room temperature by transient absorption and transient X-ray absorption spectroscopy were initially limited to porphyrins, phthalocyanines, , and dithiolato complexes of Ni II and revealed very fast decays to relaxed 3 d–d (MC) excited states. , A recent study aimed to install an emissive (metal-centered) spin-flip excited state but was not successful in that regard . Another recent study claimed that emission is observable for two octahedrally coordinated Ni II complexes in the solid state at 150 K, but the emission was unusually broad and overlapped substantially with the lowest-energy absorption bands .…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…A very recent study reported ligand-based fluorescence from a Ni II complex in solution without direct metal contribution . Weakly luminescent Ni II compounds emitting from triplet states were found in two other recent works, albeit only in the solid state, in which the processes illustrated in Figure a/b are largely suppressed. , Studies in fluid solution at room temperature by transient absorption and transient X-ray absorption spectroscopy were initially limited to porphyrins, phthalocyanines, , and dithiolato complexes of Ni II and revealed very fast decays to relaxed 3 d–d (MC) excited states. , A recent study aimed to install an emissive (metal-centered) spin-flip excited state but was not successful in that regard . Another recent study claimed that emission is observable for two octahedrally coordinated Ni II complexes in the solid state at 150 K, but the emission was unusually broad and overlapped substantially with the lowest-energy absorption bands .…”
Section: Introductionmentioning
confidence: 97%
“…77,80 Studies in fluid solution at room temperature by transient absorption and transient X-ray absorption spectroscopy were initially limited to porphyrins, phthalocyanines, 81,82 and dithiolato complexes of Ni II and revealed very fast decays to relaxed 3 d−d (MC) excited states. 83,84 A recent study aimed to install an emissive (metal-centered) spin-flip excited state but was not successful in that regard. 85 Another recent study claimed that emission is observable for two octahedrally coordinated Ni II complexes in the solid state at 150 K, but the emission was unusually broad and overlapped substantially with the lowest-energy absorption bands.…”
Section: ■ Introductionmentioning
confidence: 99%
“…In aqueous solutions, the coordinated ligand can be photochemically substituted by the water molecule (the photoaquation reaction). For example, Fehlner and Turner proposed that aqueous NiLCl 2 , where L = NH 2 (CH 2 ) 2 NH­(CH 2 ) 3 NH­(CH 2 )­NH 2 , upon LMCT excitation forms NiL­(H 2 O) 2 . The femtosecond studies of metal complexes with organic ligands have revealed another relaxation pathway of LMCT excited states, such as highly efficient internal conversion and intersystem crossing into low-lying d–d states followed by their relaxation into the ground state (GS) on femto- and picosecond time scales. The femtosecond studies of aqueous ferric hexacyanide, [Fe­(CN) 6 ] 3− , revealed two main relaxation channels following LMCT excitation: CN – elimination followed by aquation to form [Fe­(CN) 5 H 2 O] 2– and internal conversion into the vibrationally hot ground electronic state. , …”
Section: Introductionmentioning
confidence: 99%
“…31 Along with a wide range of DFT studies on this class of molecules, several ab initio studies have largely focused on predicting the singlet− triplet gap of the neutral complex. 32−36 Finally, photoelectron 37−39 and femtosecond 40 spectroscopy have recently been used to study the ionization and ultrafast dynamics of these compounds.…”
Section: ■ Introductionmentioning
confidence: 99%
“…DFT combined with X-ray absorption spectroscopy (XAS) data has shown that the ligands in these species act as the source or sink of electrons during the redox process, and the ligands are described as redox noninnocent. Ligand noninnocence is not limited to metal dithiolates, however, and generally allows the metal ions to assume unexpected oxidation states. In the case of nickel dithiolates, the metal remains in a Ni­(II) oxidation state throughout the oxidative series . Along with a wide range of DFT studies on this class of molecules, several ab initio studies have largely focused on predicting the singlet–triplet gap of the neutral complex. Finally, photoelectron and femtosecond spectroscopy have recently been used to study the ionization and ultrafast dynamics of these compounds.…”
Section: Introductionmentioning
confidence: 99%